The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/0218492309348504
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Continuous Venovenous Hemofiltration during Coronary Surgery

Abstract: Postoperative continuous venovenous hemofiltration decreases acute renal failure in patients with moderate renal dysfunction undergoing coronary artery bypass grafting, but it prolongs intensive care unit stay. We developed a simple method to connect a hemofiltration machine to the cardiopulmonary bypass system. To evaluate the benefit of intraoperative hemofiltration, 124 consecutive patients (mean age, 67 +/- 6 years) with moderate renal dysfunction were studied. Surgery was preformed between January 2005 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
0
15
0
4
Order By: Relevance
“…One study evaluated the effect of prophylactic hemofiltration on postoperative renal function in 124 consecutive patients with moderate preoperative renal dysfunction. The results showed that the patients with intraoperative prophylactic hemofiltration had better protection of renal function than the patients in the group without prophylactic hemofiltration [123]. A retrospective observational multicenter study enrolled data from 24 Spanish hospitals with 203 patients with AKI-RRT after cardiac surgery.…”
Section: Prophylactic and Therapeutic Blood Purificationmentioning
confidence: 99%
“…One study evaluated the effect of prophylactic hemofiltration on postoperative renal function in 124 consecutive patients with moderate preoperative renal dysfunction. The results showed that the patients with intraoperative prophylactic hemofiltration had better protection of renal function than the patients in the group without prophylactic hemofiltration [123]. A retrospective observational multicenter study enrolled data from 24 Spanish hospitals with 203 patients with AKI-RRT after cardiac surgery.…”
Section: Prophylactic and Therapeutic Blood Purificationmentioning
confidence: 99%
“…A retrospective cohort study of 220 patients (aged 10 days to 19 years) demonstrated that an increase in Hb of >3g/dL from preoperative value on POD 1 was a significant risk factor (adjusted OR:6.94 [95% CI 2.33-20.69]) in the development of CS-AKI. 29 The effect of other modifications in CPB techniques, such as utilization of pulsatile CPB, 127 ultrafiltration, 128 and hemofiltration 129 during CPB on CS-AKI have only been predominantly described in the adult cardiac population. However, these have not been widely studied in children.…”
Section: Specific Strategies Of Cpb Supportmentioning
confidence: 99%
“…и подключением ГФ во время ИК, СКФ по сле КШ снижалась незначительно, была сравнима с та ковой при операциях КШ «of pump». В группе ИК без ГФ, СКФ после операции была достоверно ниже [7]. В наше исследование включено меньше пациентов, кроме операций КШ имели место вмешательства на клапанах сердца и левом желудочке, доза замещения несколько больше, чем в приведенном исследовании.…”
Section: результаты и обсуждениеunclassified
“…В качестве профилактики ухудшения функции почек, развития послеоперационной ОПН у больных высоко го риска предложена интраоперационная ГФ [7]. В слу чае развития ОПН, процедуры ЗПТ применяют на ос новании абсолютных показаний и оценки тяжести ОПН согласно классификаций RIFLE (2004), AKIN (2007) [8].…”
unclassified